Base case simulation of a semi-batch emulsion copolymerization process: application to styrene/ butadiene system - I Harsono; H Hindarso; N Indraswati (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2005)
It has been long recognized that emulsion polymerization is a complex heterogeneous process involving transport of monomers, free radicals, and other species between aqueous phase and organic phase. Though there are a number of models available in the literature, most of them deal only with specific aspects in emulsion polymerization and are far from being general. To simulate this complicated process and to achieve an adequate level of understanding, a Polymers Plus software from Aspen Technology. Inc. was used. The objective of this work is to illustrate the principle of use of Polymers Plus, simulate, and analyze the free-radical seeded emulsion copolymerization of styrenebutadiene process model in a semi-batch reactor. The base case simulation can be used to gain process understanding by analyzing how process variables and operating conditions during the course of a semi-batch reactor affect the product quality.Keywords: Polymers Plus, Emulsion Copolymerization, Simulation, Semi Batch Reactor, Styrene/ butadiene AbstrakTelah diketahui sejak lama bahwa polimerisasi emulsi merupakan sebuah proses heterogen yang kompleks, yang meliputi perpindahan monomer, radikal bebas, dan senyawa lainnya dalam fasa air dan fasa organik. Walaupun dalam literatur terdapat berbagai model, sebagian besar hanya membahas tentang aspek-aspek khusus dalam polimerisasi emulsi yang belurn berlaku umum. Untuk melakukan simulasi serta meningkatkan pemahaman tentang proses yang kompleks ini, digunakan perangkat lunak Polymers Plus dari Aspen Technology, Inc. Penelitian ini bertujuan untuk memberikan ilustrasi tentang prinsip penggunaan Polymers Plus serta melakukan simulasi dan analisis tentang model untuk proses kopolimerisasi emulsi styrene-butadiene dengan free radical seeded dalam reaktor semi batch. Simulasi ini dapat digunakan untuk memperoleh pemahaman proses dengan menganalisis pengaruh variabel-variabel proses dan kondisi operasi dalam reaktor semi batch terhadap kualitas produk.Kata Kunci: Polymers Plus, Kopolimerisasi Emulsi, Simulasi, Reaktor Semi Batch, Stiren/ butadien